Ethnic Tourism: A Case Study of Language and Culture Preservation of the Bateq Indigenous Group of Orang Asli in Peninsular Malaysia - Lah, Salasiah Che (EDP Sciences, 2014)
Malaysia provides ethnic tourism which is related to the more popularly known as nature or eco-tourism where an indigenous or traditional group of people who live in this environment will interact with and provide services to the tourists who would like to experience ethnic tourism. Ethnic tourism refers to travel motivated by the search for the first hand, authentic and sometimes intimate contact with people whose ethnic and/or cultural background is different from the tourists. Tourists are also driven by the desire to see some of the threatened cultures that may soon disappear through assimilation into the nation's majority. This paper aims to explore ethnic tourism as a preservation strategy for language and culture in a selected community of Bateq Orang Asli group in Peninsular Malaysia in relation the language and cultural preservation of this community. An in-depth interview, a qualitative research technique, was selected as a method of data collection. The multimedia data was also collected including the recordings of the indigenous languages, still pictures and videotapes of the indigenous and cultural activities. The findings of this study show that the Bateq Orang Asli groups have preferences of their languages even though there is a pattern that a high number of lexical items have been borrowed from Malay. Language shift among younger speakers is also becoming a trend. In terms of the preservation of cultural heritage, the Bateq Orang Asli are still very positive about keeping their practices and lifestyles. The involvement of Bateq Orang Asli in promoting ethnic tourism in the surrounding areas near their settlements has contributed to their language and cultural preservation.